1993
DOI: 10.1111/j.1365-2141.1993.tb03100.x
|View full text |Cite
|
Sign up to set email alerts
|

The presence of messenger RNA for HLA class I in human platelets and its capability for protein biosynthesis

Abstract: In order to determine whether platelets contain specific messenger RNA encoding for HLA class I molecules, polymerase chain reaction (PCR) was performed with RNA from different platelet donors. Two amplified 300 bp and 279 bp cDNA fragments were obtained which encompassed sequences from 321 to 620 and from 795 to 1073. The 300 bp fragment encodes exon 2 and exon 3, the 279 bp encodes a portion of exon 4, exon 5, exon 6 and a portion of exon 7. A 300 bp nested PCR product from one donor, that encoded for the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 33 publications
0
30
0
1
Order By: Relevance
“…Platelets are peculiar in that they are, first, relatively short-lived (~7 days half-life); second, they are the smallest cells of blood, and third, although without a nucleus, they exhibit active RNA metabolism and are translationally active [25]. During thrombopoiesis, anucleated platelets are derived from megakaryocytes in the bone marrow and are released into the bloodstream.…”
Section: Introductionmentioning
confidence: 99%
“…Platelets are peculiar in that they are, first, relatively short-lived (~7 days half-life); second, they are the smallest cells of blood, and third, although without a nucleus, they exhibit active RNA metabolism and are translationally active [25]. During thrombopoiesis, anucleated platelets are derived from megakaryocytes in the bone marrow and are released into the bloodstream.…”
Section: Introductionmentioning
confidence: 99%
“…Blood platelets, as cytoplasmic fragments of megakaryocytes, lack nucleus, but have been shown to contain RNA (Ault et al, 1992) and possess biosynthetic activity for the major platelet proteins (Kiefer et al, 1987). By the use of polymerase chain reaction (PCR), the presence of metabolically stable mRNA in human platelets was documented for some of the platelet proteins (Konkle et al, 1993;Matsuda et al, 1993;Mehta et al, 1995;Santoso et al, 1993), as well as the possibility of detecting changes in platelet mRNA levels in some pathologies (Matsuda et al, 1993). The existence of mRNA for platelet 5HT transporter was demonstrated in humans using Northern blot analysis and confirmed by reverse transcriptase-PCR (Lesch et al, 1993a).…”
Section: Discussionmentioning
confidence: 91%
“…It has been shown that platelets retain mRNA from megakaryocytes [41]. It has also been shown that platelets contain rough endoplasmic reticulum and polyribosomes, and de novo protein biosynthesis can occur in platelets (including translation of HLA) [42,43]. In addition, platelets contain the 20S proteasome [44,45].…”
Section: Discussionmentioning
confidence: 97%